Prevalence of G6PD Deficiency in Children with Hepatitis A - Ghasem Miri-Aliabad; Ali Khajeh; Tooran Shahraki (International Journal of Hematology-Oncology and Stem Cell Research, 2017)
Introduction: Hepatitis A virus is the most prevalent viral hepatitis. It is globally a major public health problem with different clinical symptoms. This study aimed at investigating the clinical findings and prevalence of glucose 6-phosphate dehydrogenase (G6PD) deficiency in children with hepatitis A. Materials and Methods: In this prospective study, demographical information, clinical findings, and G6PD level of hepatitis A patients, who were visited at Pediatric Hematology clinic, were entered into the database. The diagnosis of hepatitis A infection was based on the presence of anti-HAV IgM antibody. The activity of G6PD enzyme was measured with florescent spot test. Results: Of the 117 children with hepatitis A, 52 (44.4%) were male and 65 (55.6%) were female. The mean age of these patients was 2.79±5.39 years. The most prevalent clinical manifestations were dark yellow urine and anorexia. G6PD deficiency was observed in 26 (26.3%) out of 99 patients whose G6PD levels were measured. Conclusion: Given the high prevalence of G6PD deficiency in this study, the measurement of G6PD level along with other liver and biochemical markers in areas with endemic hepatitis A is recommended. In addition, it is recommended that patients undertake precise monitoring for hemolysis and renal function.